Last of the empires - John L.H. Keep (Oxford University Press, 1995)
Making use of a broad literature of "sovietological" expertise along with the new information made available since Soviet secrecy was relaxed in 1988, Last of the Empires sums up what is now known about postwar Soviet history and presents it in a clear and coherent narrative